Getting better? The effect of the single supervisory mechanism on banks' loan loss reporting and loan loss reserves - Kim Ristolainen (Bank of Finland, 2022)
The recent financial crises have brought into focus questions regarding the quality of banks’ assets. We study the patterns in banks reserving for and reporting of loan losses in the EU before and after implementation of the Single Supervisory Mechanism (SSM). We find that banks that 1) have less tier 1 capital, 2) are smaller, 3) are less liquid and 4) have smaller net interest margins either report relatively smaller loan loss reserves or less loan losses, even after including various controls. This supports the hypothesis that financially weaker banks may have a larger incentive to engage in balance sheet window dressing. We further find that the SSM has reduced but not eliminated the under-reserving and under-reporting bias. In addition, there has been a separate positive effect on the overall proportion of nonperforming loans (NPLs) that are realised as losses among the banks that have been under direct supervision by the SSM since implementation of the SSM.